2017
DOI: 10.3389/fmicb.2017.01513
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Rubella Virus Strains Detected Around the Time of the 2012–2013 Epidemic in Japan

Abstract: A nationwide rubella epidemic occurred from 2012 to 2013 in Japan, resulting in around 17,000 rubella cases and the birth of 45 infants with congenital rubella syndrome. The aim of this study was to genetically characterize the rubella viruses (RVs) circulating around the time of the epidemic in Japan. In total, 221 RV strains detected from 14 prefectures in Japan between 2010 and 2014 were sequenced in the 739 nucleotide-window region within the E1 gene. The virus strains were chronologically and geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Although Japan is on its way to achieving substantial herd immunity to prevent rubella epidemics , adult men aged 39-56 years are known to have missed vaccination in childhood, and those aged 28-38 years have only had the opportunity for one vaccination dose. As a consequence, the country remains prone to imported cases and experienced a rubella epidemic during 2012-14 (Mori et al, 2017). Moreover, owing to the absence of an identifiable increase in the proportion of rubella antibody-positive individuals following the 2012-14 epidemic (Nishiura et al, 2015), another epidemic began in August 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Although Japan is on its way to achieving substantial herd immunity to prevent rubella epidemics , adult men aged 39-56 years are known to have missed vaccination in childhood, and those aged 28-38 years have only had the opportunity for one vaccination dose. As a consequence, the country remains prone to imported cases and experienced a rubella epidemic during 2012-14 (Mori et al, 2017). Moreover, owing to the absence of an identifiable increase in the proportion of rubella antibody-positive individuals following the 2012-14 epidemic (Nishiura et al, 2015), another epidemic began in August 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The vaccination history of the subject was investigated by public health officers. The viral genotypes were determined by a phylogenetic analysis based on the 739‐nucleotide window region within rubella virus E1 gene using reported primer sets . A total of 300 RT‐PCR‐positive rubella patients were examined for rubella‐specific IgM titer.…”
Section: Summary Of Participants Enrolled In This Studymentioning
confidence: 99%
“…We amplified the E1 protein-coding region genome of the virus and sequenced the molecular window region (739 nt) ( 7 ). We classified this rubella strain into genotype 1E and deposited it into GenBank (RVs/Osaka.JPN/41.17[1E], accession no.…”
mentioning
confidence: 99%
“…LC333396). We generated a phylogenetic tree including 61 strains using the maximum-likelihood method ( Figure ); it revealed that rubella virus can be classified into 5 distinct lineages (L0–L4), as previously described ( 7 , 8 ). 1E-L1 strains are mainly detected in China and Russia.…”
mentioning
confidence: 99%
See 1 more Smart Citation